2002
DOI: 10.1088/0952-4746/22/3/302
|View full text |Cite
|
Sign up to set email alerts
|

A model for evaluating radiological impacts on organisms other than man for use in post-closure assessments of geological repositories for radioactive wastes

Abstract: Bioaccumulation and dosimetric models have been developed that allow the computation of dose rates to a wide variety of plants and animals in the context of the deep geological disposal of solid radioactive wastes. These dose rates can be compared with the threshold dose rates at which significant deleterious effects have been observed in field and laboratory observations. This provides a general indication of whether effects on ecosystems could be observable, but does not quantify the level of those effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus in Thorne et al (2002) radiological impact on organisms other than man of various long-lived radionuclides of importance was evaluated in solid waste disposal sites (in geological repositories). Threshold dose rate for the induction of significant deleterious effects on communities is estimated and it has been found that compliance with the radiological protection standards appropriate to man ensures that such thresholds are not exceeded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in Thorne et al (2002) radiological impact on organisms other than man of various long-lived radionuclides of importance was evaluated in solid waste disposal sites (in geological repositories). Threshold dose rate for the induction of significant deleterious effects on communities is estimated and it has been found that compliance with the radiological protection standards appropriate to man ensures that such thresholds are not exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed a conclusion about correctness of the anthropocentric principle. Thorne et al (2002), however, adopted a common dose limit for all the selected non-human species (10 mGy day ÿ1 or 3.65 Gy a ÿ1 ), which was considered to be an analogue of a dose of 1 mSv a ÿ1 for man. In other words, in that paper less stringent standards of permissible biota exposure were adopted than in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of scenarios may trigger a radiological assessment of nonhuman biota. For example, this may occur in the context of environmental site remediation , radioactive waste disposal (Thorne et al, 2002), or nuclear power plant accidents (Warner and Harrison, 1993).…”
Section: Problemmentioning
confidence: 99%
“…Thorne et al 2002) have used elsewhere precalculated absorption energy fractions for photons and electrons in order to give more realistic values of internal dose. Thorne et al (2002) note that internal exposure of animals has been estimated by calculating the dose at the centre of a uniformly contaminated sphere of unit density material. Obviously, such a positioning of a receptor has a tendency to overestimate the dose.…”
Section: Introductionmentioning
confidence: 99%